2003
DOI: 10.1080/00050060310001707137
|View full text |Cite
|
Sign up to set email alerts
|

Employee assistance programs: a review of the management of stress and wellbeing through workplace counselling and consulting

Abstract: Employee Assistance Programs (EAPs) provide counselling and consulting services that focus on the prevention and/or remediation of personal problems experienced by employees, or members of their families. EAPs are currently considered one of the main vehicles for occupational stress management and are rapidly evolving into providers of holistic wellbeing programs in the workplace. This form of service delivery has, however, been criticised for focusing interventions at the individual rather than at the organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 30 publications
1
91
0
1
Order By: Relevance
“…Given the rapid expansion of employee counselling in the US and the UK over recent years, it is surprising that there remains a lack of rigorous research into the individual and organizational benefits of such schemes as identified as recently by McLeod (2001). Kirk and Brown (2003) reinforce McLeod's view and state ''EAP evaluations have not yet produced the quality of evidence that would enable an unqualified endorsement of EAP interventions in the management of stress and other personal and organisational issues in the workplace'' (p. 141). Kirk and Brown (2003) claim that this may have more to do with research designs in the workplace, an issue which is not unique to EAP evaluations, rather with the deficiencies with the nature of the services provided by EAPs.…”
Section: New Researchmentioning
confidence: 74%
See 2 more Smart Citations
“…Given the rapid expansion of employee counselling in the US and the UK over recent years, it is surprising that there remains a lack of rigorous research into the individual and organizational benefits of such schemes as identified as recently by McLeod (2001). Kirk and Brown (2003) reinforce McLeod's view and state ''EAP evaluations have not yet produced the quality of evidence that would enable an unqualified endorsement of EAP interventions in the management of stress and other personal and organisational issues in the workplace'' (p. 141). Kirk and Brown (2003) claim that this may have more to do with research designs in the workplace, an issue which is not unique to EAP evaluations, rather with the deficiencies with the nature of the services provided by EAPs.…”
Section: New Researchmentioning
confidence: 74%
“…Counselling Providers are extremely reluctant to grant access on the grounds of client confidentiality, but the reality is they simply do not want the intrusion (Kirk & Brown, 2003). There is no shortage of studies reported in the literature on EAPs; however, the majority of these so called ''evaluations'' comprise case studies in a single organizational setting, and are often conducted by the providers of the service, either internal or external who have some investment in the outcome (Cooper & Cartwright, 1994;Kirk & Brown, 2003). Client organizations are generally uninterested in supporting such independently conducted evaluations Kirk, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some went further to present job stress as one of the most common problems or a primary area for EA professionals (Rich, 1987;Van Den Bergh, 2000;Yamatani, Santangelo, Maue, & Heath, 1999), a key reason for employers to have EAPs (Lee, 2005;Rich, 1987), or the leading reason that employees contacted a particular EAP (Masi & Jacobson, 2003). In fact, some have even suggested that growth in EAPs may be largely due to employer recognition of stress as a workplace phenomenon (Kirk & Brown, 2003).…”
Section: Resultsmentioning
confidence: 95%
“…even when clients described problems that were work-related." Kirk and Brown (2003) noted that the tendency "to ignore the role of the workplace" as a causal factor in employee's behavioral problems is among "the most vehement criticisms of EAPs. "…”
Section: Body and Soulmentioning
confidence: 98%